Drivers of post-fire Nothofagus antarctica forest recovery in Tierra del Fuego, Argentina - Ruggirello, Matthew Joseph; Bustamante, Gimena; Fulé, Peter Z.; Soler, Rosina (Frontiers in Ecology and Evolution, 2023)
Large wildfires were historically absent in the forests of Tierra del Fuego, southern Argentina. This has changed in recent decades as humans have increased ignition sources and warmer, drier periods have fueled large, severe wildfires. As a result of its location at an extreme southern latitude, Tierra del Fuego has very low tree species diversity. One of the region’s dominant tree species, Nothofagus antarctica, is thought to have traits that may make it resilient to wildfire (e.g., ability to resprout prolifically). This study examined post-fire N. antarctica regeneration across an environmental and time-since-fire gradient. Plots were established in burned (n=80), and unburned (n=16) areas in and around a wildfire that occurred in the 1940s and another that occurred in 2019. Seedling and sapling regeneration densities were measured, as were environmental (e.g., slope) and fire-impacted variables (e.g., distance to mature live trees). Seedling densities were lower in burned plots than in controls, with this trend being exacerbated in the 2019 fire with increasing distance from mature live trees (ρ = -0.5, p < 0.001). Regeneration occurred generally in clumps and principally through basal sprouting from live and top-killed individuals, with not all top-killed individuals resprouting. Seedling densities were most strongly impacted by time since fire (z = 3.31, p < 0.001), distance to mature live trees (z = -3.73, p < 0.001), and post-fire canopy cover (z = 2.37, p = 0.02). Sapling densities were modulated by slope (z = 1.96, p = 0.05), time since fire (z = 4.85, p < 0.001), and distance to mature live trees (z = -4.57, p < 0.001). Despite lower regeneration densities in recently burned plots and less live basal area and canopy cover in older burned plots when compared to unburned controls, burned stands appear to be on a trajectory to recover pre-fire characteristics, although this recovery is spatially variable. Still, full recovery has not occurred 80 years after the 1940s fire. Currently, these burned areas resemble grasslands or savannas. They do not provide the habitat or ecosystem services that denser forests do and may require active restoration to fully recover pre-fire characteristics.